Nekotorye aspekty podgotovki rossijskich sportsmenov k XXIV Olimpijskim zimnim igram 2022 goda v Pekine (KNR) - Melnikova, N. Yu.; Treskin, A. V.; Melnikov, V. V.; Melnikova, A. N.; Yuryev, Yu. N. (Vestnik sportivnoj nauki; Sports science bulletin, 2020)
From February 4 to February 20, 2022 in Beijing (China) will take place the XXIV Olympic Winter Games. Effective preparation and quality provision of participation of Russian athletes in the Games of 2022 are among priorities for state organizations and public associations in the field of physical culture and sports. Competitive programs of the Olympic Winter Games are constantly improving. Over the past seven Olympic cycles, since 1994, the number of sets of medals played has increased significantly. Thus 61 sets of medals were played at the 1994 Olympic Winter Games in Lillehammer, Norway, 102 at the 2018 Games, and 109 sets of medals will be played at the 2022 Games. New sports disciplines (7 sets of awards) are included in the program of Games 2022: monobob (women), bobsleigh - 1 set of awards; mixed team relay, short rack - 1; mixed team competitions, ski jumping - 1; acrobat mixed team competitions, freestyle - 1; big air (men and women), freestyle - 2; snowboard cross mixed team competitions, snowboard - 1. As the number of sets of Olympic awards increases, competition increases and, as a result, requirements and approaches to ensuring training change to actually qualify for the highest Olympic awards.